Applications of Pattern Recognition - Travieso-Gonzalez, Carlos M. (IntechOpen, 2021)
Nowadays, technological advances allow the development of many applications in different fields. In this book, "Applications of Pattern Recognition", two important fields are shown. The first field, data analysis, is a good tool to identify patterns; in particular, it is observed by a stereoscopic calculation model based on fixation eye movement, a visual interactive programming learning system, an approach based on color analysis of Habanero chili pepper, an approach for the visualization and analysis of inconsistent data, and finally, a system for building 3D abstractions with wireframes. On the other hand, automatic systems help to detect or identify different kinds of patterns. It is applying to incomplete data analysis a retinal biometric approach based on crossing and bifurcation, an Arabic handwritten signature identification system, and finally, the use of clustering methods for gene expression data with RNA-seq.